Digital transformation of major scientific meetings induced by the COVID-19 pandemic: insights from the ESC 2020 annual congress. Issue 4 (23rd August 2021) - Roffi, Marco; Casadei, Barbara; Gouillard, Christine; Nambatingué, Nata; Daval, Ghislain; Bardinet, Isabel; Priori, Silvia G
Abstract: As a consequence of the COVID-19 pandemic, the European Society of Cardiology (ESC) was forced to pivot the scientific programme of the ESC Congress 2021 into a totally new format for online consumption, The Digital Experience . A variety of new suppliers were involved, including experts in TV studio, cloud infrastructure, online platforms, video management, and online analytics. An information technology platform able to support hundreds of thousands simultaneous connections was built and cloud computing technologies were put in place to help scale up and down the resources needed for the high number of users at peak times. The video management system was characterized by multiple layers of security and redundancy and offered the same fluidity, albeit at a different resolution, to all user independently of the performance of their internet connection. The event, free for all users, was an undisputed success, both from a scientific/educational as well as from a digital technology perspective. The number of registrations increased by almost four-fold when compared with the 2019 record-breaking edition in Paris, with a greater proportion of younger and female participants as well as of participants from low- and middle-income countries. No major technical failures were encountered. For the first time in history, attendees from all around the globe had the same real-time access to the world's most popular cardiovascular conference. Graphical Abstract: